2005
DOI: 10.1139/s04-036
|View full text |Cite
|
Sign up to set email alerts
|

Low pressure ultraviolet inactivation of pathogenic enteric viruses and bacteriophages

Abstract: To elucidate the roles of physical and chemical properties of viruses and their sensitivity to UV radiation, the kinetics and extent of inactivation of several waterborne pathogenic viruses and bacteriophages with different virion sizes and genomic composition by monochromatic, low-pressure (LP) UV was determined in phosphate buffered saline or a filtered drinking water. The inactivation rates of the small RNA viruses, poliovirus 1 and Coxsackievirus B4, by LP UV were very rapid and reached ~4 log10 and >5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…Intact Ascaris eggs were highly resistant to UV radiation; a fluence of 1,000 J/m 2 was required to achieve 1-log inactivation. This fluence is two to four times higher than the fluences required to inactivate adenoviruses (13,24,36,39), which are the most UV resistant of the human enteric viruses that have been studied. Thus, according to the methods used in our research, Ascaris eggs are the most UV-resistant water-related pathogen identified to date.…”
Section: Discussionmentioning
confidence: 92%
“…Intact Ascaris eggs were highly resistant to UV radiation; a fluence of 1,000 J/m 2 was required to achieve 1-log inactivation. This fluence is two to four times higher than the fluences required to inactivate adenoviruses (13,24,36,39), which are the most UV resistant of the human enteric viruses that have been studied. Thus, according to the methods used in our research, Ascaris eggs are the most UV-resistant water-related pathogen identified to date.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, nuclear excision repair has been reported to be involved by human fibroblast host cells and human KB cells on UV-irradiated adenovirus serotype 2 (8,32,33), suggesting that there are host cellular mechanisms that may correct damaged viral DNA. Indeed, because adenovirus has been shown to have the lowest rate of inactivation by UV light among all other waterborne viral, bacterial, and protozoan pathogens (13,17,26,29,38,41,43,50), the repair mechanism has been, in fact, suggested to be a reason for the high resistance to UV of adenovirus (15).…”
Section: Discussionmentioning
confidence: 99%
“…Human adenovirus serotype 2 strain adenoid 6 (VR-846; ATCC, Manassas, VA), was used as a model virus for this study (38). The virus stock was propagated in human lung carcinoma A-549 cells (CCL-185; ATCC, Manassas, VA) before use in experiments according to the following protocol, with the exception of experiment UV-1 using the virus stock directly upon shipment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptosporidium, Giardia) at relatively low, economical doses, and due to the absence of any known harmful disinfection by-products. While most viruses are more difficult to inactivate with UV light than bacteria or protozoa, a UV dose (or 'fluence') of 40 mJ/cm 2 applied by collimated beam exposures at bench-scale has been shown to successfully achieve 4-log inactivation of many waterborne viral pathogens including echovirus, coxsackievirus, calicivirus, and poliovirus Gerba et al 2002;Shin et al 2001;Meng and Gerba 1996).…”
Section: Introductionmentioning
confidence: 99%